What Do We Do When We Discuss? A Micro‐genetic Analysis of Couples' Conflict. Issue 1 (March 2016) - Fossa, Pablo; Molina, María Elisa; de la Puerta, Sofía; Barr, Michelle; Tapia‐Villanueva, Luis
Abstract : This article focuses on dialogic discursive dynamics present in couples' conversations about unresolved conflicts. The phenomenon of conflict is addressed as a semiotically mediated process of co‐construction of the self and the relationship. The purpose of this article is to report on patterns of meaning construction in couples' conflict, with the identification of strategies that promote or hinder resolution. A qualitative exploratory approach was used to focus on the interactional process at the micro‐processing level. Eight married couples participated in the study. The procedure considered asking the couple to discuss unresolved conflict. Recorded data of couples' dialogues were transcribed to text and assessed through semiotic analysis using a microgenetic protocol (Molina, Del Río, & Tapia, 2015). The results document the use of strategies for conflict regulation such as psychological distancing, opposition, and generalisation on the border between protecting the bond and regulating tension. The dynamics of non‐resolution manifested in polarisation and rigid patterns with increased tension. The 'in‐motion' nature of dialogue about conflict is pushed by the semiotic tension that induces variations in subjective positions manifested in speech and actions.